Studies on Neotropical crickets: Crinklyalis n. gen., a new cricket genus (Orthoptera: Phalangopsidae: Paragryllinae) from the foothills of theColombian Andes - Cadena-Castañeda, Oscar J.; García, Alexander García; Castellanos, Maria Del Pilar; Tavares, Gustavo Costa (Zootaxa, 2023)
A new genus of small phalangopsids (Orthoptera: Phalangopsidae) from the foothills of the Colombian Andes is described. Crinklyalis n. gen. is distinguished from the other genera of the subtribe Strogulomorphina (Paragryllini) by the modification in the mesal region of the tegmina, apparently an acoustic chamber; reduction of wing venation; male genitalia tubular, elongated and mostly membranous, with only the distal section sclerotized. Additionally, the key for the identification of the genera of the subtribe was updated, and the morphology of the new genus was discussed, as well as distributional gaps that currently exist for the Strogulomorphina taxa.